Features of conduction electrons motion in the field of coherent light beams - Semchuk, O.Yu.; Willander, M.; Karlsteen, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
Conduction electrons moving in a non-homogeneous field of coherent light beams (CLB) are investigated. It is shown that a conduction electron simultaneously takes part in two oscillations. More exactly, an electron oscillate with the frequency w and in addition, it carry out a forced oscillation with the frequency wz << w (w is the CLB frequency) inside a one-dimensional potential well that is induced in the semiconductor by the CLB.